The Study of Development of Science and Technopark (STP) in Indonesia - Noor Arifin Muhammad; Muhyiddin Muhyiddin; Ade Faisal; Istasius Angger Anindito (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
Development of Science and Technopark (STP) is one of the priorities in the RPJMN 2015-2019, with the target of building 100 STPs. The target is very ambitious and realistically cannot be achieved if the STP standards follow what has been established in the world such as Ideon Science Park (Sweden), Tsing Hua University Science Park (China), Daedeok Innopolis (Korea) and other STPs. Moreover, many proposals from various regions and ministries with a limited actual operational scope such as household industry centers, research demo plot, work-training center, etc., ask to transform into STPs following Government programs. Whereas through quick assessment only the proposed sites are mostly not potential locations to be developed as STP. For this purpose, best practices analysis of some of the world’s leading STPs is established to determine the standard requirements and the components that must be completed so that a site has the potential to be STP. Then, an analysis of some potential STP candidates in Indonesia related to development progress and future prospects was carried out. The end goal of this study is a general policy recommendation and roadmap for the development of STPs in Indonesia in accordance with STP standards.